2015
DOI: 10.1111/dth.12207
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of thromboangiitis obliterans (Buerger's disease) with high-potency vasodilators

Abstract: Thromboangiitis obliterans (TAO) or Buerger's disease is a vascular inflammatory thrombotic occlusive and segmental disease affecting distal small and medium-sized arteries of the limbs. Tobacco is the main trigger factor and avoiding it is the main treatment. Frequently, it is necessary to use high-potency vasodilators, such as iloprost, bosentan, sildenafil, or alprostadil, to relieve symptoms and reduce the risk of amputation. Iloprost is the only one that has been shown to be effective in randomized clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Many diff erent vasodilating agents have been proposed for acute management of patients with TAO, although iloprost is the only one that has been evaluated in randomized trials. Intravenous (IV) iloprost has been recommended as a fi rst-line treatment [21] and there are recent data suggesting that it may lead to good results even without smoking cessation, concurring with our results as well [22]. In a recent systematic review, evaluating fi ve randomized trials [23], IV iloprost has been found to be superior to aspirin or even per os iloprost, concerning symptoms recession and ulcer healing in patients with TAO.…”
Section: Discussionsupporting
confidence: 85%
“…Many diff erent vasodilating agents have been proposed for acute management of patients with TAO, although iloprost is the only one that has been evaluated in randomized trials. Intravenous (IV) iloprost has been recommended as a fi rst-line treatment [21] and there are recent data suggesting that it may lead to good results even without smoking cessation, concurring with our results as well [22]. In a recent systematic review, evaluating fi ve randomized trials [23], IV iloprost has been found to be superior to aspirin or even per os iloprost, concerning symptoms recession and ulcer healing in patients with TAO.…”
Section: Discussionsupporting
confidence: 85%
“…Arteriography is the main diagnostic test and biopsy is rarely indicated. [1,7,8] These patients have a high risk of disability and amputation. [8] In a study described a risk of amputation of 11 to 23%.…”
Section: Discussionmentioning
confidence: 99%
“…[3] More recently, bosentan has been introduced in refractory cases of TAO, bringing in a new alternative for prolonged oral treatment. [915] …”
Section: Discussionmentioning
confidence: 99%
“…[4,915,17] After evaluation of the full text, 2 of these articles were excluded because they were reviews. [4,17] In addition, we excluded 7 of the 19 cases reported by De Haro et al [11] because their clinical characteristics were not sufficiently detailed to be individually analyzed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation